Encimi iz naddružine kratkoverižnih dehidrogenaz/reduktaz kot nove farmakološke tarče - Brunskole Švegelj, Mojca (Farmacevtski vestnik, 2009)
Short-chain dehydrogenases/reductases (SDR) constitute a large protein family.Although they have several structural features in common, they act on ahighly diverse set of substrates. They are involved in metabolism of steroid hormones, fatty acids, alcohols, retinoids, prostaglandins and xenobiotics. Around 70 SDR members are identified within the human genome. In human body they participate in numerous distinct (patho)physiological processes, thus they are very interesting therapeutic targets for the treatment of genetic, hormone dependent and metabolic diseases like galactosemia, phenylketonuria, breast cancer, endometrium, prostate and colon cancer, dyslipidemia, obesity and arterial hypertension.
Keywords: dehidrogenaze; encimi; hormoni; metabolizem; reduktaze